2010
DOI: 10.1016/j.healthpol.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Applying upstream interventions for interpersonal violence prevention: An uphill struggle in low- to middle-income contexts

Abstract: a r t i c l e i n f o Keywords:Interpersonal violence prevention policy Risk factors Interventions Burden of disease Low-to middle-income contexts Western Cape South Africa a b s t r a c tIn South Africa's Western Cape province, interpersonal violence was identified among the key prevention priorities in the provincial government's Burden of Disease (BoD) Reduction project. To date, there are no adequate systematic reviews of the full range of potential intervention strategies. In response, available data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
(47 reference statements)
0
36
1
Order By: Relevance
“…Interventions which directly target high-risk groups such as repeat offenders are relatively easy to evaluate through experimental study design (Rosenberg et al 2006). Hence, the effects of proximal, as opposed to distal, interventions may be more prominently represented in the literature because they are relatively easy to demonstrate (Limbos et al 2007;Matzopoulos et al 2010). Upstream interventions, instead, often address less clear-cut risk factors such as education, employment and living conditions, and are therefore more difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions which directly target high-risk groups such as repeat offenders are relatively easy to evaluate through experimental study design (Rosenberg et al 2006). Hence, the effects of proximal, as opposed to distal, interventions may be more prominently represented in the literature because they are relatively easy to demonstrate (Limbos et al 2007;Matzopoulos et al 2010). Upstream interventions, instead, often address less clear-cut risk factors such as education, employment and living conditions, and are therefore more difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
“…This second aspect informed a multi-sectoral violence prevention approach for the province. The review identified numerous examples of other upstream interventions which have been deemed promising and have relevance in the Western Cape, where new and innovative solutions to the high rate of interpersonal violence need to be found (Matzopoulos, Bowman, Mathews & Myers 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although many of these patients will have recurring substance-related injuries [10], most have never sought formal substance abuse treatment [11]. Screening patients in EDs for substance use-related problems, and providing brief interventions (BIs) to at-risk patients may reduce the likelihood of further substancerelated injuries [12].…”
Section: Introductionmentioning
confidence: 99%
“…Second, apart from a few studies [33][34][35][36], knowledge of how RTC informs response to BIs within the ED population is limited. Given the significant burden on the health care system posed by ED patients with substance-related problems [12], there is a need to better understand this population's response to BIs for substance use.…”
Section: Introductionmentioning
confidence: 99%
“…As such, they can be difficult to sustain over relatively short political cycles. [9] Reducing firearm mortality by means of stricter gun control is one of the most important short-to medium-term measures to address the burden of violence in SA, while longer-term interventions and policy options take effect. When we have evidence that policies and interventions are working, we need to ensure that they are applied rigorously and consistently.…”
mentioning
confidence: 99%